Analisis nilai tambah UD. Chikanos Food di Kelurahan Kendari Caddi Kecamatan Kendari Kota Kendari - Rosnita; La Ola, La Onu; Rosmawati; Huli, La Ode; Risfandi; Patiung, Seventry Meliana (Jurnal Sosial Ekonomi Perikanan, 2024)
This study aims to determine the added value created by UD. Chikanos Food in Kendari caddi Village, Kendari District, Kendar City. This research was conducted in March 2023 at UD. Chikanos food. The method used in this research is the case study method with the case analysis of added value in processed marlin fish at ud.chikanos food with a total of 7 respondents. Data obtained through observation, interviews, documentation, literature review. The method used in this study uses quantitative methods with data analysis used is the analysis of added value, value of wages/salaries, depreciation, taxes, and profit/profit. Based on the results of the research, it is known that the process of processing marlin fish into fish balls and otak-otak through several processes such as the process of preparing tools and materials, the manufacturing process, the packaging/quality process, and the marketing process, the amount of added value created by UD. Chikanos food on marlin fish processing for 1 month with 7 production times is IDR 51,087,450.